2017
DOI: 10.1002/jhbp.453
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of perioperative antimicrobial therapy based on the results of preoperative bile cultures in patients undergoing biliary reconstruction

Abstract: This study demonstrated that preoperative bile culture-targeted administration of prophylactic antibiotics decreased SSIs following HBP surgery with biliary reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 33 publications
(47 reference statements)
6
69
0
Order By: Relevance
“…The proportion of patients in whom A hydrophila was isolated was therefore low compared with other bacteria, such as Enterococcus, Escherichia, Pseudomonas, Klebsiella, and Enterobacter species. 11 As had been previously reported, however, in the current study A hydrophila infection showed potential to develop into lethal POIC. 12 As for surgical procedures, there was no mortality among our patients that underwent cholecystectomy and hepatectomy without biliary reconstruction.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The proportion of patients in whom A hydrophila was isolated was therefore low compared with other bacteria, such as Enterococcus, Escherichia, Pseudomonas, Klebsiella, and Enterobacter species. 11 As had been previously reported, however, in the current study A hydrophila infection showed potential to develop into lethal POIC. 12 As for surgical procedures, there was no mortality among our patients that underwent cholecystectomy and hepatectomy without biliary reconstruction.…”
Section: Discussionsupporting
confidence: 59%
“…Assessment of bacteria species and their antibiogram spectrum and selecting or combining appropriate antibiotics with consideration of pathogenicity of each bacterium could therefore be important. 11 In this cohort, one patient died due to sepsis, although he had been preoperatively confirmed to have isolation of A hydrophila. Several other major bacteria were confirmed in this case and the appropriate antibiotics for A hydrophila were not chosen.…”
Section: Discussionmentioning
confidence: 83%
“…Evidence suggests that PBD can improve immune functions and nutritional sta-Early intraabdominal infection following pancreaticoduodenectomy bacterial contamination. A randomized controlled trial conducted by Okamura et al demonstrated that preoperative bile culturetargeted administration of prophylactic antibiotics decreased surgical site infections in hepatobiliarypancreatic surgery with biliary reconstruction 26) .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some descriptions of a higher incidence of liver abscess after biliary-enteric anastomosis [12] , or endoscopic interventions such as papillotomy and stent implantation, have been reported because bacterial invasion of the bile duct may occurr after loss of protection by the papillae [4] . A high frequency of surgical site infections (SSIs) after hepato-pancreatic-biliary (HBP) surgery, including biliary reconstruction, was also reported in a trial of antimicrobial therapy [13] . Because 40% of Japanese cases had HBP surgery with biliary reconstruction, prophylactic antibiotics could be considered to avoid this critical condition, if the patient has other systemic risks.…”
Section: Discussionmentioning
confidence: 95%